Direito à saúde da pessoa com deficiência o papel dos planos privados de saúde na persecução desse direito fundamental - Monteiro, Luciana de Vasconcelos Gomes (2017)
The present study aims to develop a reflection about the performance of private health plans in the promotion of the right to health of people with disabilities, in order to identify the role of health plans in the realization of this right. In order to base the study in question and favor its better understanding, the work is divided into three chapters, arranged in a balanced manner. Firstly, an approach is taken on the person with Disabilities, discussing some elements of the historical course of protection of their rights, through the legal instruments that stood out most in the search for the consolidation of these rights. The focus is given to the International Convention on the Rights of Persons with Disabilities, which presents itself as an important instrument of protection, against discrimination and promotion of social inclusion, and served as a basis for the elaboration of the Brazilian Inclusion Law, which emerges as the result of the struggles of the social movements of people with disabilities in Brazil, in the search for recognition of their rights. Its main objective is to promote the equalization of opportunities for people with disabilities. So that they have autonomy in the performance of their basic activities, and have access to the services available to all citizens. The next chapter addresses the right to health as a fundamental social right, thus secured as a right of all and duty of the State. When it was pointed out about the dimensions of fundamental rights and their guiding principles; In addition to considering the right to health of the disabled person, who should enjoy the highest possible health status without suffering for that reason. Finally, it was about the supplementary health, referring to the medicalhospital service offered by the private assistance network. When the structure and regulation of supplementary health in Brazil was highlighted; In addition to the health care provided by the private network for people with disabilities, and the characteristics of the care provided to them.